ORGANISASI DAN KOMITMEN LOCUS OF CONTROL ATAS PARTISIPASI PENYUSUNAN ESTIMASI TERHADAP KINERJA PEMERINTAH KOTA BANDAR LAMPUNG - Sanusi, Anuar (Jurnal Manajemen dan Keuangan, 2011)
Moderated regression analysis is used to determine of the interaction effect (Chen don cohen, 1983; Arnold, 1982; 1984; cnampoux and petres, 1987; hartmaon and Moers, 1999) between the estimate participation and the leadership style on managerial performance. Based on the approach adopted by Govindarajan and Gupta (1985), to answer hypothesis 1 and 2 are mathematically shown by equation (1) and (2) as follows that y = bo + b1 X1 + X2 + B 2 e, and y = bo + b1X1 + X2 + b2b3 X1X2 + e. Meanwhile, to answer the third hypothesis, it is indicated by equation (3) and (4) as follows that Y = bo + b1X1 +b3x3 + e, and Y = bo + b1 X1 + b2X2 + b2b3X1X2 + e. The results of research that are shown by coefficients table has indicated: 1) High participation in the estimate arranging influences the increasing of managerial performance on the government, 2) Locus Of Control influences the estimate participation arranging in managerial performance of local government improvement for 0.291, 3) Excellent leadership style in the estimate arranging influences the increasing of local government managerial performance for 0.22, 4) Locus of control (x1) and leadership style (x2) have contributed simultaneously and significantly toward the participative estimate arranging (y). The results of research above explain that locus of control (x1) and leadership style (x2) have simultaneously influenced the participative estimate arranging (y) about 60%. The rest of 40% is the influences that come from the other factors, 5) Locus of control (x1), leadership style (x2) and the estimate participation arranging (y) have contributed simultaneously and significantly to the participative estimate arranging (y). The results of research above also explain that locus of control (x1) and leadership style (x2) have simultaneously influenced the participative estimate arranging (y) on the performance of local governments (z) about 55%. The rest of 45% is the influences that come from the other factors. Keywords: Organizational Commitment, Locus of Control, The estimate Participation Arranging and Performance.